1998
DOI: 10.1021/bi971959a
|View full text |Cite
|
Sign up to set email alerts
|

Two Nonmuscle Myosin II Heavy Chain Isoforms Expressed in Rabbit Brains:  Filament Forming Properties, the Effects of Phosphorylation by Protein Kinase C and Casein Kinase II, and Location of the Phosphorylation Sites

Abstract: During the course of the expression of a 47-kDa COOH-terminal fragment of brain-type nonmuscle myosin heavy chain (MIIBF47), we found two closely related forms of MIIB, designated MIIB alpha and MIIB beta, in rabbit brains. The B alpha form corresponded to SMemb, described by Kuro-o et al. [(1991) J. Biol. Chem. 266, 3768] and was the more abundant form in rabbit brain, while the B beta form was novel. MIIB beta F47 differed from MIIB alpha F47 at six positions, three of which were within the carboxyl-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
3
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(143 citation statements)
references
References 39 publications
(93 reference statements)
6
132
3
2
Order By: Relevance
“…In favor of this view, Burridge and coworkers suggested that the activation of myosin II activity produces the force driving the formation of stress fibers and focal adhesions (Chrzanowska-Wodnicka and Burridge, 1996). Because stress fibers are thought to attach to the focal adhesions that provide the force required for anchoring them to the cell matrix , it is therefore likely that the decrease in the myosin II-driven force by the phosphorylation of MLC 20 at the inhibitory sites influences the formation of focal adhesions as well as the stress fibers.Previous in vitro biochemical studies have suggested that the phosphorylation of myosin II at the nonhelical tail plays a role in the disassembly of myosin filamentous structures (Murakami et al, 1998(Murakami et al, , 2000Dulyaninova et al, 2005). In the present study, the expression of S1A/S2A MLC 20 attenuated the PDGF-induced disassembly of stress fibers (Figure 5), whereas the expression of ⌬C-Myosin IIB did not significantly change the disassembly of stress fibers (Figure 6).…”
supporting
confidence: 46%
See 3 more Smart Citations
“…In favor of this view, Burridge and coworkers suggested that the activation of myosin II activity produces the force driving the formation of stress fibers and focal adhesions (Chrzanowska-Wodnicka and Burridge, 1996). Because stress fibers are thought to attach to the focal adhesions that provide the force required for anchoring them to the cell matrix , it is therefore likely that the decrease in the myosin II-driven force by the phosphorylation of MLC 20 at the inhibitory sites influences the formation of focal adhesions as well as the stress fibers.Previous in vitro biochemical studies have suggested that the phosphorylation of myosin II at the nonhelical tail plays a role in the disassembly of myosin filamentous structures (Murakami et al, 1998(Murakami et al, , 2000Dulyaninova et al, 2005). In the present study, the expression of S1A/S2A MLC 20 attenuated the PDGF-induced disassembly of stress fibers (Figure 5), whereas the expression of ⌬C-Myosin IIB did not significantly change the disassembly of stress fibers (Figure 6).…”
supporting
confidence: 46%
“…Moreover, it was recently reported that myosin II isoforms (IIA and IIB) differentially contributes to the cell motility (Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), suggesting that myosin isoforms are regulated by distinct mechanisms in motile cells. Supporting this notion, biochemical studies revealed that phosphate incorporation of MHC-IIB by PKC is much faster than that of myosin IIA and, in contrast, that filament assembly of myosin IIA is regulated by its binding protein (Mts1) but not that of myosin IIB (Murakami et al, 1998(Murakami et al, , 2000Dulyaninova et al, 2005). To clarify the roles of phosphorylation of MLC 20 and MHC on actomyosin dynamics in distinct cellular domains will be the subjects of future work.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Exactly how these observations fit alongside the expected decline in activity following specific Ser1937 phosphorylation by PKCζ (Even-Faitelson and Ravid 2006) remains unclear, but the observed differences presumably relate to the consequences of phosphorylation at additional sites by PKCγ (Rosenberg and Ravid 2006). PKCβII (Table 1) phosphorylates the HCs of both M2A and M2B; the former on Ser1917, a site close to the nonhelical tailpiece but still within the helical domain (Ludowyke et al 2006), and the latter at multiple sites within the nonhelical tailpiece (Murakami et al 1998). PKCβII-dependent phosphorylation of the M2A HC in RBL-2H3 Mast cells occurs as a consequence of antigen binding to IgE and the phosphorylation time-course parallels degranulation (Ludowyke et al 2006).…”
Section: The Players: Binding Partners and Regulationmentioning
confidence: 60%